2014
DOI: 10.4161/nucl.32235
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar stress with and without p53

Abstract: A veritable explosion of primary research papers within the past 10 years focuses on nucleolar and ribosomal stress, and for good reason: with ribosome biosynthesis consuming ~80% of a cell’s energy, nearly all metabolic and signaling pathways lead ultimately to or from the nucleolus. We begin by describing p53 activation upon nucleolar stress resulting in cell cycle arrest or apoptosis. The significance of this mechanism cannot be understated, as oncologists are now inducing nucleolar stress strategically in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
288
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(300 citation statements)
references
References 278 publications
(464 reference statements)
9
288
1
2
Order By: Relevance
“…Nevertheless, p53 knockdown does not alter PARP cleavage nor the mitochondrial depolarization in PPAN-depleted cells, revealing that PPAN-mediated apoptosis functions independently of p53. Interestingly, yeast is also sensitive to stress, although p53-dependent stress-response mechanisms do not count, because yeast lacks p53 and MDM2 proteins (44). Consequently ancestral, the so far unraveled modes of p53-independent stress response could exist, which were retained in higher organisms as a safety mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, p53 knockdown does not alter PARP cleavage nor the mitochondrial depolarization in PPAN-depleted cells, revealing that PPAN-mediated apoptosis functions independently of p53. Interestingly, yeast is also sensitive to stress, although p53-dependent stress-response mechanisms do not count, because yeast lacks p53 and MDM2 proteins (44). Consequently ancestral, the so far unraveled modes of p53-independent stress response could exist, which were retained in higher organisms as a safety mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in C.elegans showed that depletion of the nucleolar RNA-associated protein NOL-6 induces immunity against bacteria infection through activation of CEP-1/p53, suggesting that the nucleolus can signal to CEP-1/p53 under stress conditions 58 . A homologue for Mdm2 has not been found in nematodes so it is possible that MLN4924 and ActD induced p53 activation depends strictly on the Mdm2 presence, whereas NOL-6 induced signaling depends on other E3-ligases or other mechanisms of CEP-1/p53 activity regulation (translational) 59 .…”
Section: Discussionmentioning
confidence: 99%
“…The production of ribosomal RNA occupies >50% of all eukaryotic transcription and represents the major source of cellular energy consumption, as well as being tightly coordinated with cell growth and division (Henras et al 2014). As a result, any defect in ribosome biogenesis must be rapidly communicated to the cell's proliferative machinery to prevent division of cells with insufficient translational capacity; similarly, inhibition of ribosome synthesis in response to DNA damage or other stresses is essential to prevent cellular energy depletion and/or production of aberrant ribosomes from damaged rDNA (James et al 2014;Tsai and Pederson 2014). Indeed, eukaryotic cells have developed an array of regulatory checks and balances to arrest rRNA transcription and processing under stress conditions (Boulon et al 2010) and, conversely, to induce cell cycle arrest and/or apoptosis in response to perturbation of ribosome production (termed the 'nucleolar stress response'; Suzuki et al 2012).…”
Section: Introductionmentioning
confidence: 99%